Bank Ownership and Credit Growth in Emerging Markets During and After the 2008-09 Financial Crisis : A Cross-Regional Comparison - Chen, Guodong (IMF Working Papers; Working Paper ;, 2014)
This paper examines bank credit growth in emerging markets before, during, and after the 2008-09 financial crisis using bank-level data, focusing on the role of bank ownership. Credit growth by foreign banks lagged behind that of domestic banks in 2009 in Asia, and in 2010 in Latin America and emerging Europe. State-owned banks instead played a counter-cyclical role during the crisis in particular in Latin America and emerging Europe, and credit by stateowned banks also grew faster than that of private banks after the crisis in Latin America. Expansionary monetary policy on average led to higher credit growth. Banks in Latin America and Asia that relied more on retail funding had higher credit growth, in particular during the crisis. Better-capitalized banks and banks with more liquid assets also had faster credit growth. Finally, banks in countries with stronger banking regulation had higher credit growth during the crisis.